2020
DOI: 10.3389/fvets.2020.601336
|View full text |Cite
|
Sign up to set email alerts
|

Algae-Derived Polysaccharides Promote Growth Performance by Improving Antioxidant Capacity and Intestinal Barrier Function in Broiler Chickens

Abstract: This study aimed to determine the efficacy of dietary algae-derived polysaccharides (ADPs) from Enteromorpha on growth performance, intestinal morphology, intestinal permeability, and antioxidant capacity in serum, liver, and intestinal mucosa of broilers. Three hundred and ninety six day-old male chicks were randomly assigned to six dietary treatments containing 0 (Control), 1,000, 2,500, 4,000, 5,500, and 7,000 mg ADP/kg basal diet in a 35 day feeding trial. During day 1–21, compared with the control group, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 42 publications
6
60
0
Order By: Relevance
“…Previous studies have shown that the nutritional composition of C. vulgaris may contribute to their effects on mitigating metabolic alterations through different mechanisms [ 36 , 37 ]. Several algae-derived bioactive compounds, like lipids, antioxidants, pigments, vitamins and polysaccharides are known to have beneficial effects on human and animal health [ 38 40 ]. In contrast, here, data suggest that both feed carbohydrate-degrading enzymes (Rovabio ® and the pre-selected four-CAZyme mixture) were effective to hydrolyse C. vulgaris cell wall polysaccharides that changed fibre gut profile, thus reducing its anti-hyperlipidaemic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the nutritional composition of C. vulgaris may contribute to their effects on mitigating metabolic alterations through different mechanisms [ 36 , 37 ]. Several algae-derived bioactive compounds, like lipids, antioxidants, pigments, vitamins and polysaccharides are known to have beneficial effects on human and animal health [ 38 40 ]. In contrast, here, data suggest that both feed carbohydrate-degrading enzymes (Rovabio ® and the pre-selected four-CAZyme mixture) were effective to hydrolyse C. vulgaris cell wall polysaccharides that changed fibre gut profile, thus reducing its anti-hyperlipidaemic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Arabinoxylan from wheat bran has been found to increase the number of goblet cells, which secretes not only mucin but also protein barrier factors, hence protecting intestinal epithelial cells. Similarly, algae-derived polysaccharides supplementation enhanced antioxidant capacity and intestinal barrier functions in broiler chickens [ 85 ]. Dietary pectin inclusion upregulated the IL-12 expression in the ileal mucosa to increase interferon-γ production in cecal tonsils and decreased the invasion of sporozoides in ileal enterocytes during infection with Eimeria maxima .…”
Section: Effects Of Dietary Fiber On the Immune Systemmentioning
confidence: 99%
“…The positive effect was reflected in an improvement of the gain-to-feed ratio in pigs, due to an inhibition of pro-inflammatory processes in the intestine and to antimicrobial effects. An improvement in growth performance may be related to the improvement of immune defence and suppression of excessive apoptosis among intestinal epithelial cells, as observed in piglets [64] and poultry [65]. Another action of antioxidants is represented by an improvement of food status and animal feed intake as some plant extracts enhance the flavour and palatability of feed, which improves feed intake and productive performance [66,67].…”
Section: Antioxidants and Their Importance In Food-producing Animalsmentioning
confidence: 99%